Treasure hunt - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery, 2013)
A hail of bullets interrupts a period of dead calm. An elderly brother and sister open fire on the plaza below their apartment, punishing the people of Vigàta for their sins. News cameras capture Montalbano<U+2014>gun in hand<U+2014>as he scales the building to capture the ancient snipers. Inside he finds a nightmarish world of religious objects and a well-worn inflatable sex doll that will come back to haunt him. The Inspector is hailed as a hero after the televised adventure and calm returns. But Montalbano begins to receive cryptic messages in verse, challenging him to go on a "treasure hunt." Intrigued, he accepts, treating the messages as amusing riddles<U+2014>until they take a dangerous turn.